Memristor spice model for designing integrated circuits / Ahmad Fuad Adzmi - Adzmi, Ahmad Fuad (2013)
A SPICE model of the memristor would be a useful tool to analyze circuit behavior to help in developing applications of this memristor via simulation. In this paper, we incorporate a memristor SPICE model for designing memristor circuit which is focused on non-linear model and implementation with analog circuits. To describe the real device operation in a circuit simulation, a SPICE model is required. We incorporate the memristor with various window functions that have been proposed in non linear ion drift memristor devices. In investigating and characterizing the behavioral properties of memristor devices, the circuit analyses of the proposed memristor models are then studied. Then, a simple analog circuit is constructed using the model specifically a simple integrator and differentiator op-amp circuit and comparison is made between memristor implemented circuit and normal integrated circuit. The research shows the difference of memristor model and the possibilities of implementing the memristor in analog circuit. The memristor model has been simulated to give a good approximation to the real memristor. Memristor model based on Strukov window function gives minimum power dissipation with 120uw. While memristor model based on Joglekar window function give the fastest time of change of the resistance for each memristor model with 320ms. It is 49.2% faster than memristor model based on Strukov window function but in term of controlling the device, memristor model based on Prodromakis window function give a better result. Also, memristor model based on Prodromakis window function only suffer 0.11% slower speed than the memristor model based on Strukov window function. It give much better result with great extend of scalability and flexibility to the model. It also found that, changing the frequency and control parameter p will also affect the memristance behavior. In implementation of memristor with analog circuit, it shows that the existence of the memristor give better functionality to the application.